Pengaruh Kompensasi dan Disiplin Terhadap Peningkatan Kinerja Karyawan PT. Binamandiri Muliaraharja Malang - Handik Purwantoro; Yuniar Hartanti (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2022)
Human resources are important for companies in planning, management, regulation so that company goals can be achieved. So the selected human resources must be able to be trusted in achieving the company's vision and mission. good performance is to provide compensation and motivation in accordance with their responsibilities Human resources are important for companies in planning, management, regulation so that company goals can be achieved. So the selected human resources must be able to be trusted in achieving the company's vision and mission. good performance is to provide compensation and motivation in accordance with their responsibilities. In addition to compensation, work motivation also plays a very important role in a company. This study aims to determine the effect of compensation and work motivation at PT Binamandiri Muliaraharja Malang. The population of this study amounted to 35 employees of PT Binamandiri Muliaraharja Malang with the number of samples selected were all employees.In this study, the sampling technique used by the author is the Non Probability Sampling technique using the saturated sampling method. Saturated Sampling is a sampling method when all members of the population are used as samples. In this study, researchers will take all 35 employees of PT Binamandiri Muliaraharja as samples. The data collection method in this research is the questionnaire method. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that; 1. Compensation has a significant effect on employee performance at PT Binamandiri Muliaraharja Malang. 2. Work motivation has a significant effect on employee performance at PT Binamandiri Muliaraharja Malang.Keywords: Compensation, Motivation and Employee Performance.